The political economy of structural adjusment - Sapelli, Claudio (Estudios de Economía, 2016)
This paper provides a model of utility maximizing governments to explain when and why countries adopt or discontinue a structural adjustment program (SAP), in an attempt to stabilize and liberalize their economies. Assuming a rent-seeking government, the model shows that compliance with an SAP is endogenous. Consequently, the key issue is to study the factors that affect the equilibrium rent-extracting rate. The paper identifies several incentives either to announce an SAP, though without implementing it, or to reverse one. These incentives are suggested as a possible explanation for the low investment rates observed in countries implementing SAPs. The paper also argues that the implementation of an SAP for a period of time long enough to bring about structural changes in the economy would, likewise, alter the equilibrium rent-extracting rate and would consolidate reforms. The paper also analyzes the negotiations between “technocrats” and “politicians” and their consequences on the type, quality and the probabilities of success of the SAP adopted. The paper argues that orthodox theorists are the generators of high quality programs. In addition, the possible role of donor agencies in signalling the quality of the program is pointed out. The paper ascribes an important role to donor agencies in the successful achievement of an SAP, as they signal, on the one hand, the government’s long run commitment with the program and, on the other hand, the program’s quality, giving a clear-cut solution to the time inconsistency problem faced by rent-seeking governments.